Nutritional Value of Fermented Maize Stover as Feed for Ruminant - B. Wattanaklang; A. Abrar; A. Cherdthong (Jurnal Peternakan Sriwijaya, 2016)
An experiment was undertaken to determine the physical and nutritional properties, in Vitro digestibility of maize stover fermented with different levels of molasses. Maize stover was collected from the field immediately after harvesting the corn, chopped and were preserved in plastic containers under normal condition and were treated, sample fermented without additives (T1), a sample with the addition of water and 5% molasses (T2). After completion of each ensiled period, nutritional properties, in-vitro digestibility and were determined. The result reveals that crude protein (CP), dry matter (DM), ash content of maize stover were increased (P<0.05) while the crude fiber (CF) contents were decreased (P<0.01) after ensiling and the addition of molasses. The highest DM, EE, and CP content was found to be 99.52%, 10.33% and 4.56% in T2 while CF was found highest in T1 32.79%. The OMD(organic matter digestibility) and DMD (dry matter digestibility) contents were decreased by ensiling with molasses. The highest DMD, OMD, N-NH3, total VFA DMD values were observed in treatmentT1 which were 47.71%, 46.78%, 12.50%, 5.42% respectively. Therefore, it can be concluded that the addition of molasses improved and nutritional properties and preservation capacity of maize stover after 21 days of ensilingKeywords: Fermented, Maize stover, Molasses, Nutritional properties, Ruminant